Copper(II) cyclam complexes with N-propionic acid pendant arms - Kubeil, Manja; Zarschler, Kristof; Pietzsch, Jens; Kraus, Werner; Comba, Peter; Stephan, Holger (European journal of inorganic chemistry, 2015)
Four cyclam (1,4,8,11-tetraazacyclotetradecane) ligands with different numbers of N-substituted propionic acid groups lead to pentacoordinate copper(II) complexes that adopt trans-I configurations (4+1 geometry), that is, the complexes have a d ground state with significant rhombic distortion. From the structural data (X-ray diffraction analysis and electron paramagnetic resonance, UV/Vis and IR spectroscopy), as the number of secondary amine groups of the macrocyclic ring substituted with propionic acid groups increases, the distortion from square pyramidal to trigonal bipyramidal increases, and this is expected to lead to relatively low complex stabilities. This is confirmed by in vitro studies with superoxide dismutase (SOD) and human serum challenge experiments as well as by biodistribution data with the 64Cu-labelled complexes. The 64Cu-labelled complexes with cyclam monopropionic and dipropionic acid show high in vitro and in vivo stabilities, and the latter provides a comparable biodistribution profile to that of 64Cu?TETA (TETA = 1,4,8,11-tetraazacyclotetradecane-1,4,8,11-tetraacetic acid).
Gesehen am 02.06.2020